KEBIJAKAN HUKUM PIDANA PADA TINDAK PIDANA NARKOTIKA DALAM PERSPEKTIF RESTORATIF JUSTICE - Prima Sandika; Mas Agus Priyambodo (IAIN Bengkulu, 2022)
Abstract : Narcotics cases are cases of extraordinary crimes (Extraordinary Crime) which are of concern to all countries in the world, because narcotics can damage a generation of nations from a country. During the Corona Virus Disease pandemic or commonly abbreviated as the acronym COVID-19. The type of research used in this research is normative juridical with a statutory and conceptual approach. This Restorative Justice can only be applied to addicts, abusers, drug dependence, victims of abuse, and narcotics for one day use. Restorative Justice can be applied if it meets the requirements, namely when caught red-handed by Polri investigators and/or National Narcotics Agency (BNN) investigators found evidence of one-day use and also has the results of an assessment from the Integrated Assessment Team for each case file transfer.Keywords: Criminal Law Policy, Narcotics, Restorative Justice